ANALISIS PENGUKURAN KUALITAS SISTEM INFORMASI AKADEMIK UNIVERSITAS JANABADRA DENGAN METODE PIESCES - Yumarlin Yumarlin; Rizqi Mirza Fadilla (Universitas Janabadra, 2020)
Academic information system (AIS) is software used to present information and organize administration related to academic activities. Janabadra University's academic information system is a web-based system that was built with the aim of managing academic data. The research method used quantitative descriptive assessment with PIECES which was taken with the average value data on each aspect. In this study, there are 6 aspects, namely (a) performance aspects, (b) information aspects, (c) economic aspects, (d) control aspects, (e) efficiency aspects, (f) service aspects. In testing the satisfaction of academic information systems carried out through questionnaires, the results obtained from 75 respondents gave an average value for each statement reviewed on the performance aspect with an average of 3.11, on the information aspect with an average of 3.26, the economic aspect was obtained The average value is 2.65, the control aspect has an average value of 3.18, the efficiency aspect is 3.67 and the service aspect has an average value of 3.18. Based on the results of the average score of the test, the academic information system of the University of Janabadra is the most superior in the satisfaction test on the aspect of efficiency.Keywords : SIA, Universitas Janabadra, PIECES